A systematic literature review of cloud computing adoption and impacts among Small Medium Enterprises (SMEs) - Salleh, Noor Afzan; Hussin, Husnayati; Suhaimi, Mohd Adam; Md Ali, Asma (Institute of Electrical and Electronics Engineers Inc., 2018)
Although cloud computing is one of the most significant trends in information technology acquisition today, its adoption amongst the SMEs is still behind the larger conterparts. Additionally, among those that use, many face challenges to gain benefits as what is normally claimed. More research is needed to understand the issue. The purpose of this paper is to present the findings of a Systematic Literature Review (SLR) conducted related to cloud computing adoption among SMEs, particularly focusing on the post adoption stage. SLR method was employed as this method enable the review been done in a more comprehensive and rigorous manner. A total of 39 relevant articles were reviewed and the findings indicate that most past researches on cloud computing and SMEs focused on adoption, exploring factors that affect the adoption. Very few studies looked at the post adoption stage or the impacts of cloud computing on SMEs.